Game plan : a proven approach to work, live, and play at the highest level possible--for as long as possible - Mancias, Mike; Murphy, Myatt (William Morrow, an imprint of HarperCollinsPublishers, 2024)
The personal trainer to LeBron James shares his blueprint to attain peak physical and psychological performance through the right combination of nutrition, physical training and recovery with tips on stretching, breathing techniques and the benefits of naps.